2023
DOI: 10.1186/s12929-023-00966-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial impairment and synaptic dysfunction are associated with neurological defects in iPSCs-derived cortical neurons of MERRF patients

Yu-Ting Wu,
Hui-Yi Tay,
Jung-Tse Yang
et al.

Abstract: Background Myoclonic epilepsy with ragged-red fibers (MERRF) syndrome is a rare inherited mitochondrial disease mainly caused by the m.8344A > G mutation in mitochondrial tRNALys gene, and usually manifested as complex neurological disorders and muscle weakness. Currently, the pathogenic mechanism of this disease has not yet been resolved, and there is no effective therapy for MERRF syndrome. In this study, MERRF patients-derived iPSCs were used to model patient-specific neurons for investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…The latter findings are in line with the study by Sharma et al., who showed that the increased NADH/NAD + ratio was the major determinant of the plasma metabolic signature of patients with MELAS and non‐MELAS m.3243A>G mutation variant 46 . It is noteworthy that the intensity of oxidative imbalance can be associated with the level of mutation load among MELAS fibroblasts, MELAS‐induced neurons, induced pluripotent stem cells (iPSCs)‐derived MERRF‐induced neural stem cells (iNSCs) and MERRF iPSC‐derived cortical neurons as evidenced by other studies 50,52,53 . In contrast, NARP patients had decreased levels of ROS and extremely low levels of catalase (CAT) protein; however, mitochondrial superoxide level was increased together with SOD2, GPX1 and GPX2 enzymes 54 .…”
Section: Antioxidant Defence In Cellular Models Of Pmdssupporting
confidence: 88%
See 1 more Smart Citation
“…The latter findings are in line with the study by Sharma et al., who showed that the increased NADH/NAD + ratio was the major determinant of the plasma metabolic signature of patients with MELAS and non‐MELAS m.3243A>G mutation variant 46 . It is noteworthy that the intensity of oxidative imbalance can be associated with the level of mutation load among MELAS fibroblasts, MELAS‐induced neurons, induced pluripotent stem cells (iPSCs)‐derived MERRF‐induced neural stem cells (iNSCs) and MERRF iPSC‐derived cortical neurons as evidenced by other studies 50,52,53 . In contrast, NARP patients had decreased levels of ROS and extremely low levels of catalase (CAT) protein; however, mitochondrial superoxide level was increased together with SOD2, GPX1 and GPX2 enzymes 54 .…”
Section: Antioxidant Defence In Cellular Models Of Pmdssupporting
confidence: 88%
“…46 It is noteworthy that the intensity of oxidative imbalance can be associated with the level of mutation load among MELAS fibroblasts, MELAS-induced neurons, induced pluripotent stem cells (iPSCs)-derived MERRF-induced neural stem cells (iNSCs) and MERRF iPSC-derived cortical neurons as evidenced by other studies. 50,52,53 In contrast, NARP patients had decreased levels of ROS and extremely low levels of catalase (CAT) protein; however, mitochondrial superoxide level was increased together with SOD2, GPX1 and GPX2 enzymes. 54 Another study involving cybrid fibroblasts derived from NARP patients with m.9032T>C mutation, and LHON-like patients m.9029A>G defect also reported increased ROS production together with upregulated mRNA level of mitochondrial SOD.…”
Section: Cellular Models Of Pmdsmentioning
confidence: 99%
“…Myoclonic epilepsy with ragged red fiber (MERRF) is a multi-system disease characterized by progressive myoclonus and seizures [96]. One of the most common mutation among the patients with different types of mtDNA mutations is m.A8344G, which affects the mitochondrial tRNA lysine [97][98][99][100][101]. Another prominent mutation in the same gene is m.G8363A, along with the m.A3243G, m.G3255A, and m.T3291C mutations, which have also been reported to cause MERRF with a defects in tRNA leucine [57][58][59]99,102,103].…”
Section: Neurological Symptoms Cardiac Dysfunction Dyspraxiamentioning
confidence: 99%
“…Another prominent mutation in the same gene is m.G8363A, along with the m.A3243G, m.G3255A, and m.T3291C mutations, which have also been reported to cause MERRF with a defects in tRNA leucine [57][58][59]99,102,103]. Mutations in tRNA-coding genes induce the global impairment of mtDNA-encoded proteins rather than affecting certain complexes or pathways [101,104,105]. This can result in the overall dysfunction of mitochondria.…”
Section: Neurological Symptoms Cardiac Dysfunction Dyspraxiamentioning
confidence: 99%